Sri Lanka : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The paper presents key findings of the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) for Sri Lanka. Despite the country's substantial achievements in human development and the economy's external openness, several factors have impeded Sri Lanka's ability to realize its growth potential. The IMF staff considers that Sri Lanka's poverty reduction strategy constitutes an adequate policy framework to increase growth and reduce poverty. However, its successful implementation will require more work in key areas.